Роль самоменеджменту в досягненні цілей менеджера в організації - Агєєва, Ірина Вікторівна; Агеева, Ирина Викторовна; Ahieieva, Iryna (My University, 2019)
UK: У статті досліджено основні підходи до визначення самоменеджменту зарубіжними та українськими науковцями. Обґрунтовано необхідність самоменеджменту в сучасних умовах, як засобу ефективності в досягненні цілей менеджера. EN: The manager for successful professional development needs to be organized. But today, many managers do not have enough organization, commitment, and do not know how to use working time rationally. In this regard, the need for professional self-development, self-improvement, and self-education becomes especially important. As a result, self-management is one of the most promising areas for achieving effective work today. The analysis of concepts, suggests that today there is no sustainable understanding of self-management, but emphasizes the importance of this management activities for organizations. This requires a deeper understanding, determination of the role and place of self-management in the management system. Self-management is understood to mean consistent and purposeful use by the manager of methods and techniques of work in daily activities to achieve the intended goals. To do this, the manager must know what is stopping him. We have considered the potential limitations of the self-development of the manager, identified by M. Woodcock and D. Francis. According to them, the manager can evaluate their capabilities in relation to the requirements of their work and be able to find real ways to develop personal and business qualities. Noteworthy is the methodology of determining the level of self-management, which was proposed by O. Shtep. Applying its methodology, managers will be able to find ways to solve problems, as well as to motivate them to perform professional tasks effectively. We are pleased to arrange the following steps, to specify the technology for self-management, to find the right choice for satisfying the needs of creative work, so for satisfying the needs of organizing. Based on the research, it was found that managers should use different self-management methods that will allow them to learn to set and achieve goals in their professional activities, as well as to avoid unforeseen difficulties. This requires self-development, self-improvement, self-control and self-motivation.
The role of self-management in achieving objectives of the manager in the organization
Keywords: самоменеджмент; менеджер; організація; методи; саморозвиток; самовдосконалення; самоорганізація; самомотивація; self-management; manager; organization; methods; self-development; self-improvement; selforganization; self-motivation